1988
DOI: 10.2307/3430508
|View full text |Cite
|
Sign up to set email alerts
|

Neurohumoral Blood Pressure Regulation in Lead Exposure

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Studies on Ca +2 and the vascular effects of lead have shown that intracellular Ca +2 -binding sites are involved in the action of this metal in vascular smooth muscle. [ 19 20 22 ] A similar finding was reported in the case of the heart, as Ca +2 influx was observed in both atrial trabeculae and in the papillary muscles of the heart. [ 19 ] The increase in Ca +2 influx and elevation of intracellular content of Ca +2 by lead may be due to the action of this metal in altering Ca +2 transport processes, such as activation of protein kinase C (that activates Ca +2 channel opening),[ 23 ] inhibition of Na + -K + , ATP ase ,[ 11 24 ] and alteration in intracellular events.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Studies on Ca +2 and the vascular effects of lead have shown that intracellular Ca +2 -binding sites are involved in the action of this metal in vascular smooth muscle. [ 19 20 22 ] A similar finding was reported in the case of the heart, as Ca +2 influx was observed in both atrial trabeculae and in the papillary muscles of the heart. [ 19 ] The increase in Ca +2 influx and elevation of intracellular content of Ca +2 by lead may be due to the action of this metal in altering Ca +2 transport processes, such as activation of protein kinase C (that activates Ca +2 channel opening),[ 23 ] inhibition of Na + -K + , ATP ase ,[ 11 24 ] and alteration in intracellular events.…”
Section: Discussionsupporting
confidence: 60%
“…In a previous experimental study, Boscolo and his colleague[ 20 21 ] demonstrated that exposure to 60 ppm of lead increases both blood pressure and cardiac inotropism, without causing any morphological changes in the myocardium. They confirmed that chronic lead exposure affects the cardiovascular system, not only by inducing metabolic changes (such as those related to the metabolism of Ca +2 or of the high-energy phosphate pathway) which are able to produce neurohumoral disorders, but also by increasing the neuorogenic and humoral effects that may be involved in the regulation of the metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in blood pressure and an association with renal damage have also been observed after lead exposure in rodent models [36,37]. Alterations in signal transduction that involve renal pathways (eg, angiotensin and vasopressin) were reported in rat models [38-40].…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine, immune, humoral and renal mechanisms (responsible for Pb-induced arterial hypertension) have been described in previous studies on Pb-exposed workers (21,44). In this respect, workers with a short period ofPb exposure showed high increase of plasma renin activity (PRA) in response to the change of position, while there was a low PRA response and high PRA values in supine position in workers suffering from blood hypertension and/or nephrosclerosis with prolonged Pb exposure (45,46). The results of these studies on Pb-exposed workers suggest that the reduced BP increment with the change of position, along with the increased PRA in supine position of the Mn-exposed workers, may in part be explained by an increased central sympathetic tone and/or by an increased response following activation of the JG adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%